כפירה והמינים בתלמוד - בר-אשר סיגל מיכל (מחשבת ישראל, 2019)
How should we translate the term min(.im) in the Babylonian Talmud? The current scholarly trend is to avoid translating it altogether, using the transliteration instead. This article demonstrates that this practice hinders our ability to understand the intended meaning ofthe term in these stories, within the context of late antique heresy-making discourses. The article surveys the scholarly debate concerning the correct way to understand stories involving minim in rabbinic literature, and it claims that, at least with regard to several of these stories in the Babylonian Talmud, it is necessary to translate the Hebrew term as “heretics.”